(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The twentieth century has gone down in history as a period of national and religious renaissance in the Muslim countries of the East and the West. The Colonial States and nations began to analyze the reasons why society was lagging behind in development as a means of overcoming colonial oppression. In this direction, many local press publications have developed. In the press, the participants of the period reflect how they understood, and reacted to the changes in the political, economic and religious spheres, and various interpretations. The article provides information about the dynamics of the formation of the idea of reform in the XVIII-XX centuries, the concept, the reflection of different directions, the differences and similarities of the idea of reform in the XVIII-XX centuries, their differences and similarities.